Life-threatening stridor presenting in a patient with rheumatoid involvement of the larynx. Issue 4 (December 1989) - McGeehan, D F; Crinnion, J N; Strachan, D R
Abstract : A case of a female patient with extensive rheumatoid arthritis who presented to the Accident and Emergency Department with life-threatening stridor is described. Although clinical involvement of the larynx is found in over a third of patients with severe rheumatoid arthritis, acute airways obstruction is fortunately a very rare complication. Stridor is probably precipitated in the acute situation in such patients as a result of upper respiratory tract infection.